David [videorecording (DVD)] - Dawes, Brent; Portbury, Kyle; Wilson, Sam (Scriptwriter) (Angel, 2026)
David grows from a humble shepherd into a young man destined for greatness and a special relationship with God. Guided by Samuel and strengthened by his bond with his friend Jonathan, David is able to soothe a troubled king and face a life of sacrifice.